2011
DOI: 10.5581/1516-8484.20110052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the return rate of volunteer blood donors

Abstract: BackgroundTo convert first-time blood donors into regular volunteer donors is a challenge to transfusion services.ObjectivesThis study aims to estimate the return rate of first time donors of the Ribeirão Preto Blood Center and of other blood centers in its coverage region.MethodsThe histories of 115,553 volunteer donors between 1996 and 2005 were analyzed. Statistical analysis was based on a parametric long-term survival model that allows an estimation of the proportion of donors who never return for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
(24 reference statements)
1
14
2
1
Order By: Relevance
“…In the literature, the association between blood group and donation frequency has not been clearly established. A study found no significant difference in non‐return rates in regard to gender, blood type, Rh blood group and blood collection unit (Lourencon et al, ). While a multivariate analysis of the yield rate of first time donors showed that younger (16 and 17 years) and older (50+ years) donors, males, blood group O donors, and those without any initial adverse reaction were most likely to return (Notari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the association between blood group and donation frequency has not been clearly established. A study found no significant difference in non‐return rates in regard to gender, blood type, Rh blood group and blood collection unit (Lourencon et al, ). While a multivariate analysis of the yield rate of first time donors showed that younger (16 and 17 years) and older (50+ years) donors, males, blood group O donors, and those without any initial adverse reaction were most likely to return (Notari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is below the median observed in high‐income countries, (32·1 donations per 1000 inhabitants per year (range 11·2–57·8)), but is compatible with the median observed in upper middle‐income countries (14·9, range 6·7–39·7) . At the Hemocenter of Ribeirão Preto, Southeast Brazil, it is estimated that only 32% of first‐time donors return within a five‐year period for new donations .…”
Section: Introductionmentioning
confidence: 99%
“…For the prevention of blood shortages, it is essential for blood banks to design and implement adequate donor recruitment and donor retention strategies that take into account the determinants of donor return. Several studies that have assessed factors influencing donor return and donor lapse of first‐time donors or donors in general have shown that no past deferrals, no donation‐related adverse events and satisfaction with the last donation experience were associated with higher return rates overall . Many studies show a gender‐specific donor behaviour, with most data indicating a higher return rates for males , and one study reporting higher return rates for females .…”
Section: Introductionmentioning
confidence: 99%